The application of current classification systems in pediatric cytopathology: Perspectives from the pediatric cytopathology symposium at the 20th International Congress of Cytology 2019. Issue 10 (25th September 2019) - Monaco, Sara E.; Baloch, Zubair W.; Rossi, Esther Diana; Teot, Lisa A.; Wright, Colleen
Abstract : A pediatric cytopathology symposium was held at the recent 20th International Congress of Cytology, which convened in Sydney, Australia, in May 2019. This educational event brought together cytopathologists from different countries and different institutions to discuss some of the practical considerations when applying current diagnostic classification systems to cytopathology specimens from young (pediatric and adolescent) patients. Within the past decade, various classification systems have been developed to create more standardized terminology for cytopathology specimen reporting among institutions, which can lead to improved management guidelines based on evidence‐based medicine. It is well known that a majority of the peer‐reviewed publications in cytopathology discussing the usefulness of these classification schemes predominantly contain case cohorts of adult patients. Although pediatric cases are not excluded from following these diagnostic guidelines, there is less of an emphasis on this age group with respect to unique findings and management differences. Thus, discussing the role of these guidelines and their applications in pediatric cases at an international educational gathering can not only be beneficial in educating the cytopathology community about the value of applying these classification systems to pediatric populations, but also can raise awareness of unique entities in cytologic specimens obtained from young patients. Abstract : A pediatric cytopathology symposium was held at the recent 20th International Congress of Cytology 2019 (ICC 2019) that convened in Sydney, Australia. This educational event brought together cytopathologists from different countries and different institutions to discuss the practical considerations when applying current classification systems to cytopathology specimens from young (pediatric and adolescent) patients. The key points of the discussion are summarized in this article.